Sea Raiders in the Amarna Letters? - Emanuel, Jeffrey P. (Altorientalische Forschungen, 2020)
The Amarna corpus contains several references to maritime conflict and related activities in the 14 th century BCE, including blockades, the movement of troops, the capturing of ships at sea, and seaborne evacuation. While most of these are encountered in the context of conflicts between Levantine polities, there are clear references to what might on the one hand be called piracy, but on the other hand either acts of naval warfare or naval elements of a larger war effort, on both land and sea. This paper considers the martial maritime activities discussed in the Amarna letters, with particular emphasis on two uniquely controversial groups mentioned in this corpus in the context of maritime violence: the ‘ships of the men of the city of Arwad’ and the ‘ miši -men.’ While the men of Arwad are identified with a polity on the Phoenician coast, they are referred to only by this collective term, even when mentioned in lists that otherwise contain only rulers. The miši , on the other hand, are not associated with any specific name or toponym. The purpose of this study is to identify just what can be determined about the roles and affiliations of these two groups in their Amarna context in this period.